Modeling Design of Solar Heating System for Absorption Refrigeration System with Partial Loads & Studying the Collectors arrangements - Ali, Mohammed Hadi (Nahrain University College of Engineering Journal, 2013)
This paper presents a modeling design for a solar heating system to be used as a driven - powered thermal energy to a single – stage absorption cooling system using Lithium Bromide solution, by using flat – plate collectors, storage tank, auxiliary heater and 3 – way valves. The study also goes into partial load control by flowrate variation through the generator section and to study the effects of series and parallel collector's arrangement arrays on the solar heating system performance.The study is focused to evaluate the performance of the solar heating system throughout the summer season. The effects on performance have been explored for various design variables and operation conditions.In this paper, it was reached to a general formula for a collector outlet temperature arranged in series and compared to a parallel arrangement.The performance calculations indicate that:? There is no significant difference in storage tank temperature for both parallel and series arrangements.? The collector's outlet temperature wasn't greatly affected by the storage tank capacity (size).? The storage tank temperature increases with partial load? Percent increases, i.e. as the thermal load decreases.